Reproductive Health in Xeroderma Pigmentosum: Features of Premature Aging. Issue 4 (October 2019) - Merideth, Melissa; Tamura, Deborah; Angra, Divya; Khan, Sikandar G.; Ferrell, Joyln; Goldstein, Alisa M.; DiGiovanna, John J.; Kraemer, Kenneth H.
Abstract : OBJECTIVE: To assess the age at menarche and menopause of women with xeroderma pigmentosum, a DNA repair disease with premature aging, in a longitudinal natural history study. METHODS: We conducted a natural history study that reviewed medical records for gynecologic and reproductive health of all female patients with xeroderma pigmentosum aged older than 9 years examined at the National Institutes of Health (NIH). We performed gynecologic and laboratory examinations on a subset of the patients. Women in a second subset, who could not be examined, were interviewed using a questionnaire. Women who were deceased or lost to follow-up formed a third subset. RESULTS: Sixty females with xeroderma pigmentosum aged older than 9 years (median 29 years, range 10–61 years) were evaluated at the NIH from 1971 to 2018. Of these 60, 31 had history, questionnaire, record review, and gynecologic evaluation; 14 had record review and questionnaire interview by telephone; and 15 had only NIH record review. Menarche in females with xeroderma pigmentosum occurred at a median age of 12.0 years (range 9–17 years), which was comparable with the U.S. general population. Among the 18 patients with menopause, the median age at menopause of 29.5 years (range 18–49.5 years) was more than 20 years younger than in the U.S. general population (52.9 years). Premature menopause (before age 40 years) occurred in 14 of the 45 (31%) women aged 18 years or older, and primary ovarian insufficiency was documented in nine of them. There were 32 live births among 21 of the women, five of whom subsequently developed premature menopause. CONCLUSION: Females with xeroderma pigmentosum in our study had a normal age at menarche and were fertile but had increased incidence of premature menopause. Premature menopause, a symptom of premature aging, should be considered for gynecologic and reproductive health as well as implicating DNA repair in maintaining normal ovarian function. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT00001813. Abstract : Women with xeroderma pigmentosum, a rare DNA repair disease with premature aging, had normal menarche but reduced age at menopause.